Implementasi Permainan “Super Deal” dalam Pembelajaran Nahwu (Bab Tawabi’) di PP. Al-Hikmah Al-Fathimiyyah Merjosari, Lowokwaru Malang - Saraswati, Ananda Nova; Muassomah (Shaut al Arabiyyah, 2024)
The focus of the research is to determine the implementation of the "Super Deal" game, its advantages and disadvantages in learning Nahwu chapter Tawabi' at the Al-Hikmah Al-Fathimiyah Islamic boarding school, Merjosari, Lowokwaru, Malang. The research method uses a qualitative descriptive approach. Data collection techniques are questionnaires, observation and documentation. Meanwhile, the data analysis technique is systematic data reduction and analysis levels (restatement, description and interpretation). Researchers took data when the learning process took place in the Daurah Wustha 2 PP class. Al-Hikmah Al-Fathimiyah. The research results are: First, the Nahwu learning process with the "Super Deal" game has six stages (dividing groups, students reading tashrif, group selection, offering and selecting envelopes, group discussion, answer presentation). Meanwhile, the advantages of the "Super Deal" game are that it creates enthusiasm and focus, makes it easier to remember, learning is not boring, trains teamwork, active and fun learning, the class atmosphere is lively and can measure abilities, exchange ideas and help understanding. The disadvantages of the "Super Deal" game are that it lacks cost and time efficiency and the division of tasks among group members is less balanced.